Aplikasi Aljabar Geometris Pada Teori Elektrodinamika Klasik - Joko Purwanto (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2012)
In this paper geometric algebra and its aplication in the theory of classical electrodynamic will be studied. Geometric algebra provide many simplification and new insight in the theoretical formulation and physical aplication of theory. In this work has been studied aplication of geometric algebra in classical electrodynamics especially Maxwell’s equations. Maxwell’s equations was formulated in one compact equation ÑF=J. The various equation parts are easily identified by their grades.